INFLUENCE OF INCOME TAX PAYMENT AND DIVIDEND POLICY TO THE LEVERAGE POLICY IN MANUFACTURING COMPANY LISTED IN INDONESIA STOCK EXCHANGE YEAR 2012-2016 - Wahyu Yunus Arianto; Wiwit Irawati (Universitas Pakuan, 2018)
This study aims to determine the effect of income tax expense and dividend policy on leverage policy at manufacturing companies listed on Indonesia Stock Exchange 2012-2016, This study uses secondary data in the form of financial statements. The research population is listed on Indonesia Stock Exchange 2012-2016. The sampling method used is purposive sampling with the sample of research amounted to 32 companies so that the research observation amounted to 160. The analysis technique used is multiple linear regression analysis. The result of the research shows that: (1) income tax expense has significant effect on leverage policy, (2) dividend policy has no effect on leverage policy, and (3) income tax expense and dividend policy simultaneously have significant effect on leverage policy.